2013
DOI: 10.1021/bm4008343
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Assisted Osteoinductive Peptide Immobilization of Polymer Scaffolds for Enhanced Bone Regeneration by Human Adipose-Derived Stem Cells

Abstract: Immobilization of osteoinductive molecules, including growth factors or peptides, on polymer scaffolds is critical for improving stem cell-mediated bone tissue engineering. Such molecules provide osteogenesis-stimulating signals for stem cells. Typical methods used for polymeric scaffold modification (e.g., chemical conjugation or physical adsorption), however, have limitations (e.g., multistep, complicated procedures, material denaturation, batch-to-batch inconsistency, and inadequate conjugation) that dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
197
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(206 citation statements)
references
References 52 publications
7
197
2
Order By: Relevance
“…Curran et al [66] Peptide sequence Alginate Osteopontin peptide Increase in hMSC osteogenic markers Lee et al [67] HA-PLG Osteocalcin peptide Increase hMSC osteogenic markers Lee et al [68] PLGA BMP-2 peptide Increase rMSC ALP expression in osteogenic medium and promotion of ectopic bone formation in vivo Lin et al [15] RGD BCP/PLA hMSC osteogenic differentiation Shin et al [70] Molecule PLGA BMP-2 hMSC osteogenic differentiation Ko et al [71] PLLA BMP-2 hMSC osteogenic differentiation Beazley et al [16] Collagen-PLGA hybrid Collagen-binding domain derived from fibronectin (CBD-BMP4) hMSC osteogenic differentiation Lu et al [72] Methacrylamide chitosan hydrogel coated glass substrates Laminin and collagen Supported hNSC differentiation Wilkinson et al [73] PMMA-g-PEG EGF MSC osteogenic differentiation Platt et al [74] Agarose PDGF-AA MSC neural differentiation Aizawa et al [75] PCL/PCL-PEG NGF MSC neural differentiation Cho et al [76] Chitosan/collagen Ⅳ VEGF Endothelial differentiation Chiang et al [77] , Poh et al [78] , Rahman et al [79] hESC: Human embryonic stem cell; hMSC: Human mesenchymal stem cell; rMSCs: Rat mesenchymal stem cell; hNSC: Human neural stem cell; PEG: Polyethylene glycol; HA-PLG: Hydroxyapatite (HA)/poly(lactic-co-glycolic acid); BMP: Bone morphogenetic protein; PLGA: Poly(lactic-co -g lycolic acid); PLA: Poly(lactic acid); PLLA: Poly(L-lactide); PCL: Polycaprolactone; PMMA-g-PEG: Poly(methyl methacrylate)-graft-poly(ethylene glycol; BCP: Biphasic calcium phosphate; EGF: Epidermal growth factor; NGF: Nerve growth factor; PDGF-AA: Platelet-derived Growth Factor AA; VEGF: Vascular endothelial growth factor.…”
Section: Neuronalmentioning
confidence: 99%
“…Curran et al [66] Peptide sequence Alginate Osteopontin peptide Increase in hMSC osteogenic markers Lee et al [67] HA-PLG Osteocalcin peptide Increase hMSC osteogenic markers Lee et al [68] PLGA BMP-2 peptide Increase rMSC ALP expression in osteogenic medium and promotion of ectopic bone formation in vivo Lin et al [15] RGD BCP/PLA hMSC osteogenic differentiation Shin et al [70] Molecule PLGA BMP-2 hMSC osteogenic differentiation Ko et al [71] PLLA BMP-2 hMSC osteogenic differentiation Beazley et al [16] Collagen-PLGA hybrid Collagen-binding domain derived from fibronectin (CBD-BMP4) hMSC osteogenic differentiation Lu et al [72] Methacrylamide chitosan hydrogel coated glass substrates Laminin and collagen Supported hNSC differentiation Wilkinson et al [73] PMMA-g-PEG EGF MSC osteogenic differentiation Platt et al [74] Agarose PDGF-AA MSC neural differentiation Aizawa et al [75] PCL/PCL-PEG NGF MSC neural differentiation Cho et al [76] Chitosan/collagen Ⅳ VEGF Endothelial differentiation Chiang et al [77] , Poh et al [78] , Rahman et al [79] hESC: Human embryonic stem cell; hMSC: Human mesenchymal stem cell; rMSCs: Rat mesenchymal stem cell; hNSC: Human neural stem cell; PEG: Polyethylene glycol; HA-PLG: Hydroxyapatite (HA)/poly(lactic-co-glycolic acid); BMP: Bone morphogenetic protein; PLGA: Poly(lactic-co -g lycolic acid); PLA: Poly(lactic acid); PLLA: Poly(L-lactide); PCL: Polycaprolactone; PMMA-g-PEG: Poly(methyl methacrylate)-graft-poly(ethylene glycol; BCP: Biphasic calcium phosphate; EGF: Epidermal growth factor; NGF: Nerve growth factor; PDGF-AA: Platelet-derived Growth Factor AA; VEGF: Vascular endothelial growth factor.…”
Section: Neuronalmentioning
confidence: 99%
“…Eight weeks later, the modifi ed materials exhibited enhanced new bone formation around the bone defects. In another animal experiment, human adipose-derived stem cells (hADSCs) cultured on the PDA and BMP-2-modifi ed PLGA scaffold were implanted in mice skull defects, and the modifi ed materials were also found to effectively enhance new bone formation [ 56 ]. It is reported that PDA coating is a biocompatible coating which can be reduced by PDA-modifi ed PLLA of infl ammation and immune responses [ 57 ].…”
Section: Polydopamine Surface Modifi Cationmentioning
confidence: 99%
“…Osteoinductive agents aim to stimulate seeded cell migration, proliferation, and migration, and modulate immune responses, involving the stimulation of MSCs and/or osteoprogenitors to differentiate into osteoblasts. There are many osteogenic proteins that stimulate the proliferation and differentiation of MSCs and/or progenitors in vitro and in vivo [Govender et al, 2002;Giannoudis et al, 2005;Ko et al, 2013]. However, they have a short half-life, and so require either high concentrations or sustained delivery for bone tissue engineering [Itoh et al, 2001].…”
Section: Introductionmentioning
confidence: 99%